Logicism and Gödel’s incompleteness theorems - Polat, Berk. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
The view of logicism which dates back to eighteenth century when Leibniz thought that mathematical statements are nothing more than identity statements is the view that mathematics is reducible to logic. This idea brings with it several commitments about the epistemological and ontological aspects related to the nature of mathematics. In this study, the common argument that Gödel’s incompleteness theorems destroyed logicism once and for all will be considered and in the end it will be concluded that logicism is open to many interpretations, some of which can remain compatible with Gödel’s incompleteness theorems.
Keywords: Logic, Symbolic and mathematical.